2020
DOI: 10.1038/s41598-020-62026-7
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the neural basis of psychotic-like experiences in adolescence during processing of emotional faces

Abstract: contemporary theories propose that dysregulation of emotional perception is involved in the aetiology of psychosis. 298 healthy adolescents were assessed at age 14-and 19-years using fMRI while performing a facial emotion task. Psychotic-like experiences (PLEs) were assessed with the CAPE-42 questionnaire at age 19. The high PLEs group at age 19 years exhibited an enhanced response in right insular cortex and decreased response in right prefrontal, right parahippocampal and left striatal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similar to patients with psychosis, studies conducted on this population have highlighted abnormal self-and bodily experiences, sleep dysfunction, and impaired social cognition (Andorko et al, 2017;Barragan et al, 2011;Gawęda et al, 2019;Graham et al, 2015;Pionke et al, 2020). Abnormal functioning of the insular cortex has also been reported (Papanastasiou et al, 2020), suggesting that interoception is likely an area worthy of investigation. Specifically, assessing individuals' tendency to focus on, worry about, and react to internal bodily changes (i.e., interoceptive sensibility), may help highlight maladaptive attentional styles (Mehling, 2016) potentially contributing to the development of psychotic symptoms, with important implications for early detection and treatment.…”
mentioning
confidence: 76%
“…Similar to patients with psychosis, studies conducted on this population have highlighted abnormal self-and bodily experiences, sleep dysfunction, and impaired social cognition (Andorko et al, 2017;Barragan et al, 2011;Gawęda et al, 2019;Graham et al, 2015;Pionke et al, 2020). Abnormal functioning of the insular cortex has also been reported (Papanastasiou et al, 2020), suggesting that interoception is likely an area worthy of investigation. Specifically, assessing individuals' tendency to focus on, worry about, and react to internal bodily changes (i.e., interoceptive sensibility), may help highlight maladaptive attentional styles (Mehling, 2016) potentially contributing to the development of psychotic symptoms, with important implications for early detection and treatment.…”
mentioning
confidence: 76%
“…Comparison of the different subtypes of telehealth intervention in relation to relapse demonstrated the greater effectiveness of online interventions, especially videoconferencing. Thus, although it is well known that psychiatric disorders such as schizophrenia and bipolar disorders are associated with impaired processing of emotional faces [25], in most of the studies reviewed, the telematic interventions in the field of mental health that proved to be the most effective in relapse prevention were carried out using applications that included face-to-face contact with a therapist. Improvements in treatment adherence, social functioning, and quality of life have also been found through videoconferencing, even in some cases, similar to those observed in the face-to-face intervention [26].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in youth reporting PLEs have found increased limbic responses to ambivalent faces 18 or to threatening faces 19 , while others have observed decreased responses to emotional faces in the prefrontal, parahippocampal, and striatal regions 20 . In addition to their association with local activity changes, PLEs were associated with decreased amygdala–prefrontal connectivity during negative emotion processing 21 .…”
Section: Introductionmentioning
confidence: 99%